2021
DOI: 10.1002/cpdd.948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Paroxetine, a Strong CYP2D6 Inhibitor, on SPN‐812 (Viloxazine Extended‐Release) Pharmacokinetics in Healthy Adults

Abstract: SPN-812 (viloxazine extended-release) is a novel nonstimulant recently approved as a treatment for attentiondeficit/hyperactivity disorder in children and adolescents. Given that SPN-812 is metabolized by CYP2D6 and may be coadministered with CYP2D6 inhibitors, this trial investigated the pharmacokinetics and safety of SPN-812 coadministered with the potent CYP2D6 inhibitor paroxetine. In this single-sequence, 3-treatment period study in healthy volunteers, subjects received a single oral dose of 700 mg SPN-81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Importantly, the dose used in the present study (200 mg) was lower than the higher 400–600 mg/day range used in adolescent and adult studies [ 25 – 27 ], and lower than the highest approved dose (400 mg/day) in pediatric patients [ 43 ]. Despite this, the T max reported here (5 h) is consistent with previous single-dose studies using viloxazine ER 700 mg in adults [ 30 , 33 , 34 ], and chronic once-daily doses of 100, 200, 400, and 600 mg in children and adolescents [ 44 ]. Because the pharmacokinetics of viloxazine appear to be linear across the therapeutic range (data on file), the pharmacokinetic effects demonstrated here are likely to be true at the higher end of the dosing range.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, the dose used in the present study (200 mg) was lower than the higher 400–600 mg/day range used in adolescent and adult studies [ 25 – 27 ], and lower than the highest approved dose (400 mg/day) in pediatric patients [ 43 ]. Despite this, the T max reported here (5 h) is consistent with previous single-dose studies using viloxazine ER 700 mg in adults [ 30 , 33 , 34 ], and chronic once-daily doses of 100, 200, 400, and 600 mg in children and adolescents [ 44 ]. Because the pharmacokinetics of viloxazine appear to be linear across the therapeutic range (data on file), the pharmacokinetic effects demonstrated here are likely to be true at the higher end of the dosing range.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the expected inter-and intrasubject variability of viloxazine, other similar studies [30][31][32], and FDA guidance [29], a sample size of 27 was deemed sufficient to assess the study endpoints.…”
Section: Methodsmentioning
confidence: 99%
“…For full concentration-over-time plots over 72 hours, see recently reported studies in healthy adults. 11,15,16 Bioavailability (F) was assumed to be equal to 1. The following parameters were used to jointly describe the viloxazine and 5-HVLX-gluc concentrations: the apparent volume of distribution of viloxazine (V2/F), the apparent volume of distribution of 5-HVLX-gluc (V3/F), the viloxazine absorption rate constant (k a ), the viloxazine clearance (CLL), the viloxazine metabolic clearance (CLV), and the 5-HVLX-gluc clearance (CLM).…”
Section: Population Pharmacokinetic Analysismentioning
confidence: 99%
“… 10 These in vitro data are consistent with a recent clinical drug interaction study in which CYP2D6 inhibition by paroxetine, a strong CYP2D6 inhibitor, resulted in a less than 35% increase in systemic viloxazine exposure, as measured by AUC. 11 Furthermore, another clinical study found only minimal impact of CYP2D6 genetic polymorphisms on systemic viloxazine exposure: C max increased only 20% and AUC 0‐24 increased 25% in poor CYP2D6 metabolizers, relative to extensive (normal) metabolizers. 12…”
mentioning
confidence: 99%
See 1 more Smart Citation